THE EFFECT OF VLOG CONTENT YOUTUBE MEDIA ON LEARNING ENGLISH - Ikhlasa, Tazkia Nurul; Suryadi, Suryadi (IJIET (International Journal of Indonesian Education and Teaching), 2023)
The proliferation of mobile devices and online storage space has led to an explosion of learning resources, one of which is the video-sharing site YOUTUBE. There are several types of content/videos in this application, one of which is English-based Daily Vlog content. The aims of this study are (1) to find out to what extent the content of YouTube vlogs affects English mastery, and (2) to identify the types of content that have the greatest impact on English language development. For what purpose do you watch YouTube vlogs? 3. Quantitative methods are used in this study. Quantitative studies involve the collection and analysis of numerical data to characterize phenomena, identify relationships, or test hypotheses. One of these tools is a student questionnaire. To calculate the final results, researchers use SPPS (Statistical Package for the social sciences). Research shows that vlog content on the video-sharing site YouTube has a considerable impact on student's ability to understand English.